Linking EU trade and development policies: lessons from the ACP-EU trade negotiations on economic partnership agreements - Davina Makhan (Deutsches Institut für Entwicklungspolitik (DIE), 2009)
While the European Community has exclusive competence for trade policy, the competence over development policy is shared with member states of the European Union (EU).Given that trade is communitarised, it could be assumed that it is a strong instrument for the EU that can be well used for development. Trade is a particularly prominent feature of the EU's relations to the African, Caribbean and Pacific (ACP) group of developing countries, and Economic Partnership Agreements (EPA) are the envisaged new trade pillar of ACP-EU-cooperation. This study analyses the development relevance of the EU's trade policy towards the ACP countries as formulated in the EPA, with a view to drawing conclusions on how to strengthen the trade development nexus. It specifically assesses the way in which the EU as a multilevel system has operated in the EPA negotiations. It is notably argued that the EU system needs to be more flexible to respond to issues of development concern in the trade negotiations, e.g. market access and support measures for ACP states. Efforts are furthermore required to improve the coordination of European policy-making on trade and development. Both the EU's communitarian and bilateral policies will need to engage in a more complementary fashion to support productive and trading capacities in the ACP and developing countries.
Keywords: 330